Analisa Gerakan Rolling Kapal Bocor Akibat Beban Gelombang Laut Pada Kapal Bulk Carrier - Teguh Putranto; Dedi Budi Purwanto (TEKNIK, 2018)
The stability is a key requirement for the ship to sail safely. This article presents an analysis of rolling movements on bulk carrier vessels that have leaked when subjected to wave loads with heading angles of 90⁰ and 270⁰ and maximum wave height. The ship is in full load condition when the simulation and analysis is carried out with a scenario of leakage in the cargo chamber. Because the vessel with compartment leakage has trim and shaky conditions, the results of the rolling motion show differences in each direction the waves come. The 3D diffraction panel method is used to get the rolling motion of the ship as a function of time. The results of the study without sloshing effects showed that the bulk carrier had the risk of sinking if there were leaks in the two cargo chambers.